An industrial quality control study on SC&C Cosmotech, Inc. - Carandang, Regine; Javier, Nidalin; Makabali, Kristine Paula (Diliman, Quezon City College of Engineering, 2004)
A study was conducted to document and assess the Statistical Quality Control of SC&C Cosmotech, exclusive manufacturer of several Johnson & Johnsons products such as the variants of face powder, cologne, isopropyl alcohol. The focus of the study is the production of the 70% isopropyl alcohol (ISP 70%). Statistical process tools are used in the course of the study. Data from the two most frequently used production lines, Line 8 and Line 9, are gathered and summarized from the existing batch records of the company. Tests of hypotheses are conducted to determine proper rational subgroups to be used in the control charts. From the conclusions, Shewhart control charts and attributes charts are done to study the average fill volume of the nozzles with the highest average fill volume, as well as the fraction nonconforming, alcohol content, and perfume content of the finished products. Out of control points and general trends are also identified. Results indicate that the nozzles are indeed out of control.This is a major cause of shortage in the expected percent yield. However, the fraction of nonconforming units, alcohol content, and perfume content, while exhibiting out of control conditions, still fall within the company's specification limits. It is therefore recommended that control charts for each of the 14 nozzles should be done and conducted over a longer study period. Results of the process capability analysis show that the process average is offcenter. The company should take appropriate measures to achieve the target values. Furthermore, results from this study can give a good estimate of the loss in profits due to excess volume.
Meanwhile, cost analysis, using estimates from the data on hand, is done by the group. It is approximated that the company annually loses a total of 41,580,000 mL of alcohol due to overfilling and incurs an estimated loss in profit of about one million pesos. However, if the company opts to purchase a filling equipment, an annual cost of P900,000 more or less would be incurred for 15 years. Thus, it is recommended that SC&C Cosmotech, Inc. acquires a new equipment in order to minimize, or if possible, eliminate their losses due to overfilling. Implementation plans on better product handling procedures, replacement of equipment, supplier evaluation, and performance measures are also presented. First of all, the company should reinforce the rule of glove usage to minimize the most common defect found in the finished product, which is Body with Dirt. The quality auditor should also perform a random inspection of workers in areas requiring manual handling to ensure that they comply with this rule. The company should also replace the filling equipment presently used and engineering economy tools could be utilized to aid in determining the best equipment to be selected. Employee training should follow after the purchase of the new machine. Third, the placement of identification code should be changed in order to reduce defects such as Ink Smear and Illegible Code in the body of the alcohol bottle. This could be done by recalibrating the labeling/printing equipment. Fourth, the company should implement a better inspection plan for testing bottle thickness through benchmarking and at the same time, evaluate the the supplier more frequently since bottle thickness is also a crucial aspect in the fill volume of the products. Lastly, seminars emphasizing the importance of the roles of the quality inspectors and other evaluation measures should be conducted to ensure the consistency of their performances.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: SC&C Cosmotech Incorporated; Hygiene products; Quality control